P216 Tracheobronchomalacia in severe asthma. (12th November 2019) - Marquette, M; Paramasivan, C; Owen, C; Herre, J; Gore, RB; Knolle, MD
Abstract : Background: Tracheobronchomalacia (TBM) is a known asthma mimic. The prevalence and contribution to symptom of TBM in severe asthma patients is unclear. We collated data on the diagnosis and management of TBM in a cohort of severe asthma patients undergoing bronchoscopy under the East of England Severe Asthma Service. Methods: Patients with an unclear asthma phenotype or treatment failure may undergo bronchoscopy as part of their evaluation. We collected data from patients undergoing bronchoscopy over a 1 year period, including patient characteristics, procedural safety, diagnosis and management of TBM and potential impact of the TBM diagnosis on asthma treatment. Results: The total number of bronchoscopy procedures was 88, 27 male and 61 female patients. The mean age was 52 and the mean BMI 30.6 kg/m 2 . The procedure was uncomplicated for 88% of patients. The most common complication was poor tolerance of the procedure – 10%. In two cases the bronchoscopy was abandoned due to complications (bleeding, hypoxia). Note neither case had long term ill effects of the bronchoscopy. TBM was identified in 24% of patients undergoing bronchoscopy, while 2% had TBM and VCD. 60% of cases with TBM had severe disease. Of note, the TBM was only detected in 30% of patients by CT scan prior to bronchoscopy. Following physiotherapy review and management of TBM, in 2/3 of cases identified with severe disease, we were able to stop or wean asthma treatments. Conclusion: Bronchoscopy was safe and generally well tolerated. Bronchoscopy is a valuable tool in identifying additional co-morbid conditions in asthma. In our cohort, 24% of patients were identified as suffering from TBM. TBM is a known asthma mimic, and can lead to patients being misidentified as having severe asthma and receiving unnecessary and ineffective treatment. Patients benefited from physiotherapy following a diagnosis of TBM and were able to wean asthma treatments. However, we do not know the prevalence of TBM in the general severe asthma population and there are no specific outcome tools to measure the success of therapy in TBM. Further research is needed to address these questions.